HANDLE DIAMETER AND THE INFLUENCE ON THE ERGONOMICS OF CRUTCHES - Bertolaccini, Guilherme da Silva [UNESP]; Vasquez, Melissa Marin [UNESP]; Bianchi, Ana Carolina [UNESP]; Sandes, Frode Eika; Paschoarelli, Luis Carlos [UNESP]; Medola, Fausto Orsi [UNESP]; Berg, A.; Bohemia, E.; Buck, L.; Gulden, T.; Kovacevic, A.; Pavel, N. (Design Soc, 2017)
The research in the field of ergonomics can contribute to the design process of Assistive Technologies using objective and subjective data measurements. The auxiliary crutches are assistive devices commonly used in the process of rehabilitation after lower-extremity injuries. However, for many subjects, walking with crutches in not an easy and comfortable task, as the loads on the upper limbs are substantial and expose the users to potentially harmful long-term effects. In this way, the objective of this study was, first, to report the evaluation of the user-crutch interface by using an objective measurement of the subjects' muscular activity and exertion perception, and to discuss how objective data measured from the subjects can contribute for the design of the interface. Eleven able-bodied subjects participated. The test protocol consisted of 3 trials of walking with crutches, each one with a different hand diameter, namely 20 mm, 32 mm and 40 mm. Surface electromyography of forearms muscles was collected, and perceived exertion was measured using the Borg's Scale. The mean of maximum EMG values showed that the highest values activity happened in the extensor digitorum muscle using the largest handles. However, the smallest handles increase electromyography activity in the flexor digitorum superficialis muscle. Statistically significant difference was found between the smaller and the larger handle diameter. The analysis of exertion perception did not show statistical difference in any of the situations investigated. Handle diameter was shown to be a factor affecting the biomechanics of the walking with crutches. In addition, ergonomic evaluation can provide objective measurements that, ultimately, may be applied in the improvement of user-product interface.
Keywords: Axillary crutches; Walking; Electromyography; Exertion perception; Handle design